2017
DOI: 10.1007/s13770-017-0050-5
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Tensile Mode and Timing of Applying Tension to Promote Tendon Gel Regeneration

Abstract: ''Tendon gel'' secreted from a parent tendon is regenerated for tendon repair by applying tension. However, the details of the tensile stimulus have not been clarified. This study aimed to evaluate an appropriate tensile stimulus mode and the optimal timing of applying tension to promote tendon gel regeneration. Tendon gel was prepared using a film model method in mice and was preserved in vivo for 3, 5, and 10 days. Unlike tendon gel on day 3 or day 5, a fibrous structure developed in the tendon gel on day 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Furthermore, the height of this peak relates to the extent cross-linking. Therefore, no peak was found in normal mature tendons [20], as shown by our results. As highlighted by a previous study [29], while the structural stability of collagen bers is affected mostly by intermolecular cross-links rather than intramolecular cross-links, collagen bers are more strongly bound together when more bers are cross-linked in type I collagen.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, the height of this peak relates to the extent cross-linking. Therefore, no peak was found in normal mature tendons [20], as shown by our results. As highlighted by a previous study [29], while the structural stability of collagen bers is affected mostly by intermolecular cross-links rather than intramolecular cross-links, collagen bers are more strongly bound together when more bers are cross-linked in type I collagen.…”
Section: Discussionsupporting
confidence: 70%
“…As highlighted by a previous study [29], while the structural stability of collagen bers is affected mostly by intermolecular cross-links rather than intramolecular cross-links, collagen bers are more strongly bound together when more bers are cross-linked in type I collagen. In addition, mechanical stress is an essential element for maturation of collagen bers [20,30]. Kwansa et al [31] also indicated that application of a traction force promotes cross-linking between the amino-and carboxy-terminal extremities of the collagen bers, which structurally strengthen the whole collagen tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mechanical stress is essential for the maturity of collagen fibers (Urschel et al, 1988 ). Similarly, Kuzumaki et al ( 2017 ) reported that when the cross-linking reaction progressed, collagen bundles were formed by a Schiff-base cross-linking reaction, and the bundle became thicker over time.…”
Section: Discussionmentioning
confidence: 91%
“…Kuzumaki et al ( 2017 ) reported that a strong traction force applied to the tendon gel can form thick fibers. Considering these reports, it is thought that the thick fibers are more resistant to tension, and there is a possibility that the results in D15 and D20 would change if a strong force within the range that does not break the tendon gel is applied in D15 and D20.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this severe post-operative complication, various attempts have been made to prevent tendon adhesion formation [ 7 , 8 ]. During the early stages of tendon regeneration, immobilizing the tendon tissue is critical for faster healing; however, at the same time, applying mechanical load onto the tendon tissue during the healing processes has also been shown to decrease the formation of post-operative tendon adhesions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%